I am sorry : Indian bureaucracy at crossroads - Agarwal, P K (Delhi, 2008)
The book has universal application to all bureaucratic systems and will be immensely useful for insight into the working of Indian bureaucracy. It will be a handbook for trainee in-service officials, administrators and policy- makers.
Keywords: Bureacucracy